If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-9x=9-6x
We move all terms to the left:
-9x-(9-6x)=0
We add all the numbers together, and all the variables
-9x-(-6x+9)=0
We get rid of parentheses
-9x+6x-9=0
We add all the numbers together, and all the variables
-3x-9=0
We move all terms containing x to the left, all other terms to the right
-3x=9
x=9/-3
x=-3
| 3x-52=5x+14 | | 3x—52=5x+14 | | x.0.8=0.2 | | 6x+2x+6=54 | | 18x-20=3x-11 | | 17^9x=12^x-2 | | 4(x+8)+20=90 | | 8x=-1(2x-5) | | 25=-0.0035x+59 | | (22x-1)=21x | | -4/9=x+5 | | 5(12-x)=3(x+12) | | 1,000,000=2•3^x | | 5x+3.7=0.8x+2.23 | | 4x^2−8x=−1 | | -2/5+x=1/6 | | 4x2−8x=−1 | | (2x+4)=3x | | (2x=+4)=3x | | 3/4y-8=7 | | n–5=2n+4 | | 2(2x-6)=18 | | 121=(x+40)+2x | | 10x-23=86 | | -3-2n=5 | | 9x+2.7=6x+4/5 | | 2x=9=71 | | (5x-1)^2=16/25 | | 8=4.9t^2+30t | | -5(x-19)=-35 | | 8x-9.3=3.5 | | 50=44-x+2x |